2015
DOI: 10.1021/jp512280p
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Ice Nucleation in Liquid Water

Abstract: We present a density functional theory approach to investigate the thermodynamics of ice nucleation in supercooled water. Within the theoretical framework, the free-energy functional is constructed by the direct correlation function of oxygen-oxygen of the equilibrium water, and the function is derived from the reference interaction site model in consideration of the interactions of hydrogen-hydrogen, hydrogen-oxygen, and oxygen-oxygen. The equilibrium properties, including vapor-liquid and liquid-solid phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…This is consistent with the present findings for the cut-and-shifted LJ model, though only not too far from coexistence. Subsequent studies of LJ nucleation [40,70] have indicated that precritical clusters are rich in randomly stacked hexagonal planes, hence in hcp-like particles. Again, the same is found in the present investigation of the cut-and-shifted LJ model, where in the deep metastable region there is a large amount of hcp-like particles in the nuclei.…”
Section: B Various Methods To Identify the Cluster Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the present findings for the cut-and-shifted LJ model, though only not too far from coexistence. Subsequent studies of LJ nucleation [40,70] have indicated that precritical clusters are rich in randomly stacked hexagonal planes, hence in hcp-like particles. Again, the same is found in the present investigation of the cut-and-shifted LJ model, where in the deep metastable region there is a large amount of hcp-like particles in the nuclei.…”
Section: B Various Methods To Identify the Cluster Particlesmentioning
confidence: 99%
“…Indeed, a lot of work has been done already, on a variety of classical water models: ST2 [27], TIP4P (in its various declinations) [28][29][30][31][32][33], and monatomic water (mW) [28,31,[34][35][36][37][38][39]. Also the methods employed to investigate ice nucleation have been the most varied: umbrella sampling [27,31,36], seeding approach [28,30,37], mean first passage time [34], metadynamics [32], density-functional theory [40], forward-flux sampling [29,33,38], and aimless shooting [39]. While all studies agree on the main picture (i.e., that the nucleation cluster is polymorphic rather than structurally homogeneous), divergence persists on the critical size, nucleation rate, interface free energy, and importance of the various ice polymorphs in the first stages of crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Under the thermodynamic driving force, ice nucleation will occur once a sufficient number of relatively long-lived hydrogen bonds spontaneously develop at the same location to form a compact nucleus. Subsequently, the nucleus alters the shape and size until reaching a stage that allows the rapid expansion, and finally causes crystallization of the entire system [152,153,155]. As shown by the molecular dynamics simulation in Fig.…”
Section: Homogeneous Ice Nucleationmentioning
confidence: 96%
“…There are also many interests on how ice polymorphs are selected upon ice nucleation [227,228,[230][231][232]. Besides this problem of polymorph selection, the estimation of the barrier height and critical nucleus size is also an important issue and recently there have been many efforts toward this direction [229,[232][233][234][235][236][237]. A link between the so-called Widom line [238], or the thermodynamic anomalies associated with the liquidliquid transition, and the ice nucleation process was also suggested [239].…”
Section: Local Structural Ordering and Homogeneous Crystal Nucleationmentioning
confidence: 99%